A imagem como texto: reflexões sobre a festa do bumbameu-boi do maranhão por meio da fotografia - Ferreira Lopes Gonçalves, Luciléa (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article expose about the use of Bumba-meu-boi tribute in Maranhão as a place for the exercise of power by political agents. The various forms of this exercise are verified through the changes that occur in stages in the party of the ox, like the baptism, which previously had as godmother people from the community where the ox was born and currently have politicians in the role of godfather or godmother. Based on thoeries of Geography, Antropology and Sociology, is used photography as a methodological contribution of qualitative nature. This research methodology is part of the still in progress doctoral fieldwork. The text concludes that the analyzed photos are also a memory of the tribute Boi, because they reveal events of a time and space